Answer:
4 sqrt(5)
Step-by-step explanation:
7 sqrt(5) - 3 sqrt(5)
These are like terms so we can subtract
4 sqrt(5)
To simplify a radical expression 7√5 - 3√5, subtract the coefficients and keep the radicand the same. The simplified expression is 4√5.
To simplify the given expression, we need to combine the terms involving square roots. We can notice that the terms have the same radicand, which is 5. So, we can combine them by subtracting the coefficients. The simplified expression is:
7√5 - 3√5 = (7 - 3)√5 = 4√5
#SPJ3
+ 9n) + 3(4n- 7n)
Answer:
n = 0 or n = -9/16
Step-by-step explanation:
Solve for n:
2 (8 n^2 + 9 n) - 9 n = 0
Hint: | Write the quadratic polynomial on the left hand side in standard form.
Expand out terms of the left hand side:
16 n^2 + 9 n = 0
Hint: | Factor the left hand side.
Factor n from the left hand side:
n (16 n + 9) = 0
Hint: | Find the roots of each term in the product separately.
Split into two equations:
n = 0 or 16 n + 9 = 0
Hint: | Look at the second equation: Isolate terms with n to the left hand side.
Subtract 9 from both sides:
n = 0 or 16 n = -9
Hint: | Solve for n.
Divide both sides by 16:
Answer: n = 0 or n = -9/16
a = 8, b = 15, c = ?
a = 24, b = ?, c = 26
Answer:
Emil's back pack weigh now .
Step-by-step explanation:
Given:
Total Weight of backpack =
can be Rewritten as
Weight of backpack =
Weight of Book 1 =
Weight of Book 2 =
We need to find weight of back pack after removing books.
Solution:
Now we can say that;
weight of back pack after removing books can be calculated by Subtracting Weight of Book 1 and Weight of Book 2 from Total Weight of backpack.
framing in equation form we get;
weight of back pack after removing books =
Now to solve the equation we will first make the denominator common using LCM.
weight of back pack after removing books =
Now the denominators are common so we will solve the numerator.
weight of back pack after removing books =
Hence Emil's back pack weigh now .